The Combination of Blood Transfusion and Repositioning in Hemolytic Anemia Patients with Peripheral Perfusion Disorders: Case Report - Jati, Bill Ilham Mahardika; Fitria, Nita; Komariah, Mariah (Jurnal Keperawatan Profesional (KEPO), 2025)
One approach to restore hemoglobin levels was blood transfusion. Another approach to help prevent the risk of pressure ulcers was alternating the patient's position from right to left. This study aimed to describe the impact of blood transfusion and alternating right and left positioning in anemic patients with nursing problems of ineffective peripheral perfusion and risk of pressure ulcers. This study used a case report method. The sample was a male patient in an internal medicine ward. Data collection was conducted using observation, physical examination, and interviews. The patient's peripheral perfusion condition improved, accompanied by improvements in vital signs after the administration of 390 mL of PRC transfusion in two units. In addition, no damage to skin integrity was observed, and the Braden Score showed a change from 12 (high risk of pressure ulcers) to 15 (low risk) after repositioning the patient using a 90° lateral position every 1–2 hours for three days. The findings indicated that both therapies were effective in improving peripheral perfusion and reducing the risk of pressure ulcers.